2007
DOI: 10.1002/marc.200700112
|View full text |Cite
|
Sign up to set email alerts
|

Living Radical Polymerization as a Tool for the Synthesis of Polymer‐Protein/Peptide Bioconjugates

Abstract: Combinations of synthetic and natural macromolecules offer a route to new functional materials. While biological and polymer chemistry may not be natural bedfellows, many researchers are focusing their attention on the benefits of combining these fields. Recent advances in living radical polymerization have provided methods to build tailor‐made macromolecular moieties using relatively simple processes. This has led to a plethora of block copolymers, end‐functional polymers and polymers with a whole range of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
275
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(277 citation statements)
references
References 249 publications
(276 reference statements)
1
275
0
1
Order By: Relevance
“…This is the most commonly exploited approach to make protein and other biopolymer conjugates. [491][492][493][494] Note that use of functionality on 'Z' leaves the thiocarbonylthio group as a potentially degradable link at the block juncture. This may or may not be advantageous depending on the application.…”
Section: Block Copolymersmentioning
confidence: 99%
“…This is the most commonly exploited approach to make protein and other biopolymer conjugates. [491][492][493][494] Note that use of functionality on 'Z' leaves the thiocarbonylthio group as a potentially degradable link at the block juncture. This may or may not be advantageous depending on the application.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Convergent methodologies require a 80 conjugation step, where both building blocks are synthesised initially and then coupling together via ligation. Divergent approaches on the other hand require either the modification of the peptide or polymer block (to subsequently allow "growth" of the other component from first moiety) or the 85 conversion of the peptidic component into a macromonomer for subsequent copolymerisation. This latter approach, also known as "grafting through", is often not referred to as a divergent approach as the peptide sequence has already been defined prior to incorporation along the polymer backbone.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…70 Whilst useful in determining the phase space for gelation, these methods cannot be used to accurately measure the mechanical properties of the gel. Nonetheless, these methods are the most highly reported in the literature for the demonstration of 85 the formation of a gel. As a result, direct comparison between different systems is often extremely difficult.…”
mentioning
confidence: 99%
“…Ten et al reported the solid phase supported synthesis routes to obtain the oligopeptide-based RAFT agents. 20 The peptide-polymer hybrid materials were synthesized by the ATRP from resin-supported peptides by Washburn et al, 21 and the peptide-polymer bioconjugate block copolymers through the nitroxide-mediated radical polymerization (NMRP) from a solid support was shown by Wooley group. 12 In this study, we described our strategy to prepare the peptide-polymer hybrid materials by combining ATRP method with solid phase peptide synthesis.…”
Section: Introductionmentioning
confidence: 99%